PROTEIN FROM JAWLA (ACETES SPP.) AND SQUILLA (ORATO SQUILLA NEPA) - GARG, D K; NAIR, A LEKSHMY; PRABHU, P V (Fishery Technology, 2017)
A simple method of isolation of protein from jawla prawnand squilla, which does not involve any chemical treatment, isreported. The method consists in blending the jawla prawn/squilla with equal quantity of water, removal of chitinousmatter, heating the pulp at ll2Â°C for 15-20 minutes and dryingthe precipitated protein after filtration.